Análise do ensino superior em Manaus: um estudo de caso - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
The present study has as proposed to analyze the speech and for práxis of the dimensions live in the Administration and Accounting Teaching in the City of Manaus, having dimensions – the technology, curriculum, University, learning teacher and evaluation in order to raise the reflexes on manager's identity and Accountant. In the technology dimension will be analyzed the balance of the use of this technology, having in mind that it involves teacher's previous preparation, of the student, of the learning environment and of the necessary materials that will be used. In the Universities dimension will be sought the factors that can influence in the Administration and Accounting teaching. In the Teacher dimension, they will be searched your knowledge and your experience in the formation and live of the new career Na learning evaluation dimension will be analyzed the factors that interfere in the process evaluation, be exam, proof, test adopted by the teachers. The Curricular Bars so much of Administration as Accounting they involve three formation factors the basic and instrumental formation, for professional and the complementary, more the apprenticeship supervised. This way, in the curricular bars dimension had carried itself in counts the admissibility verification of discipline invasions or although each discipline is conceived as an own space of the knowledge. Besides if search which are manager's competences and accountant. O Result of five searched dimensions will be introduced in tables that will allow for about for of data in several moments. answers of the questionnaire are constituted by men and women.
Keywords: Avaliação de aprendizagem; Dimensões do ensino - Amazonas; Ensino Superior - Administração - Amazonas; Organização do ensino - Amazonas; OUTROS